Uji Pengaruh Beban Klep Buang Serta Ketinggian Input Dan Output Terhadap Efisiensi Pompa Hidram - Kurniawan, Yoga Bagus; Triyono, Sugeng; Amien, Elhamida Rezkia; Tusi, Ahmad (abe.fp.unila.ac.id, 2023)
Water is a natural material that is very important for humans, animals and plants. Apart from being used as consumption, water can also be used as an energy source, with the need for water use which is very important for humans, it needs to be supported by an increase in water supply. Water supply usually uses a pump that functions to raise water from a lower place to a higher place. However, there are still many people who still have difficulty meeting their water needs due to the weak purchasing power of the people to buy pumps, especially in rural areas. Therefore, it is necessary to design a hydraulic ram pump which is one solution to overcome this problem because it is cheap and simple to manufacture and maintain. A hydraulic ram pump is a pump that can raise water from a low place to a higher place using energy that comes from the water flow itself. To find out the performance of the hydraulic ram pump, a pump efficiency test was carried out with the treatment of different heights of water flow sources, different heights of water lifted and different exhaust valve loads. The results of efficiency testing are obtained that the higher the water flow source the greater the efficiency, the lower the water lift the greater the efficiency and the lightest load on the exhaust valve has the greatest efficiency. Keywords: water, pump, hydraulic ram pump, efficiency